Science Learning Based on the MIKiR Approach Assisted by WhatsApp for Junior High School Students - Prastyo, Erwin (Proceeding International Conference on Science and Engineering, 2021)
Abstract. The Covid-19 pandemic has created various learning challenges. WhatsApp as one of the most popular messaging applications supports improvement communication between the teachers and students in distance learning during the Covid-19 pandemic. The MIKiR apparoach is one of the learning approaches that consists of four stage namely Mengalami (experiencing), Interaksi (interaction), Komunikasi (communication), and Refleksi (reflection). This study aims to analyze the implementation of the MIKiR approach on science learning assisted by WhatsApp. The method used in this research is descriptive qualitative approach. This research was conducted in MTs Darul Ishlah Sukorejo, Kendal Regency, Central Java. The subject of this research was 25 seventh grade students. Technique of collecting data was through observation, questionnaires, and documentation. The results showed that the students carried out science learning using the MIKiR approach. This study concluded that students have done active learning by applying four stages, but the quality of implementation must be improved. The participation of each students is varied due to the difference of availability of mobile device, internet network access includes data package, parental support, and self-motivation.